(Dis)satisfaction with Public Services: A Dynamic Model - Bello, André (Revista Latinoamericana de Opinión Pública, 2021)
This article assesses the effect of the economy on mass satisfaction with public services. Its central empirical contribution is a national index of satisfaction with basic government services – health, education, security, housing, transportation, employment, environment, and Bolsa Família – from 1989 to 2017 estimated with the dyad-ratios algorithm. Results show that unemployment rates, GDP growth and the prospective egotropic assessments of the economy impact satisfaction with public services. As such, this study connects two major research agendas – the quality of democracy and the macro polity.